Spectroscopic slicing to reveals internal redox gradients in electricity- producing biofilms - Robuschi, Luciana (2012)
Wired-up bacteria: Confocal Raman microscopy in combination with 3D structural analysis is used in the measurement of redox gradients in electricity-producing biofilms in vivo. The approach provides new relevant information for the understanding of electron conduction mechanisms in these systems.